Influence of diet on the prevention and treatment of Alzheimer: an integrative review (Research, Society and Development, 2023)
Introduction: Alzheimer's disease (AD) is a neurodegenerative disease that ranks as the most common form of dementia in the elderly. Faced with this and the lack of effective drug treatment, it is investigated how different diets and food groups are able to modulate and curb the pathology and development of the disease. Objective: to analyze the influence of specific diets and their components in the prevention or protection against the worsening of Alzheimer's Disease. Method: This is an integrative review on the subject of food as a protective and treatment factor in Alzheimer's disease. The search will be carried out using the keywords: Alzheimer's disease, ketogenic diet, Mediterranean diet, food, treatment and prevention. The articles were read successively, and subsequently analyzed according to the grouping of information, creating three thematic units. Results: the consumption of specific diets and foods can cause changes in the evolution of Alzheimer's disease, among these are ketogenesis-inducing foods, the Mediterranean diet and its variants such as the Mediterranean diet-DASH Intervention for Neurodegenerative Delay (MIND) and the Modified Mediterranean-style ketogenic diet (MMKD). Conclusion: it can be said that diets based on fruits, vegetables, red meat, fish and other foods present in ketogenic and Mediterranean diets have potential effects in reducing the aggravations of Alzheimer's disease.